A Multifunctional Nanocomposite Hydrogel for Endoscopic Tracking and Manipulation. (20th March 2020) - Augurio, Adriana; Cortelletti, Paolo; Tognato, Riccardo; Rios, Anne; Levato, Riccardo; Malda, Jos; Alini, Mauro; Eglin, David; Giancane, Gabriele; Speghini, Adolfo; Serra, Tiziano
Abstract : Multifunctional Hydrogels In article number 1900105, Adolfo Speghini, Tiziano Serra, and co‐workers report the fabrication of a 3D printed multi‐responsive and hierarchically organized material for deep monitoring and remote manipulation. This light and magnetic field responsive hydrogel holds promise for the generation of advanced bionic devices.